Investigation of Causal Effect of Type 2 Diabetes Mellitus on Lung Cancer: A Mendelian Randomization Study - Hong, Tongtong; Qin, Na; Zhao, Xiaoyu; Wang, Cheng; Jiang, Yue; Ma, Hongxia; Dai, Juncheng (Frontiers in Genetics, 2021)
Background Although several observational studies have attempted to investigate the association between type 2 diabetes mellitus (T2DM) and lung cancer risk, the results are controversial. Here, we intend to examine whether there is a causal association between T2DM and lung cancer risk. Materials and Methods We conducted a Mendelian randomization (MR) study to systematically investigate the effect of T2DM on lung cancer among 13,327 cases and 13,328 controls. A weighted genetic risk score (wGRS) was constructed as a proxy instrument by using 82 previously reported T2DM-related single nucleotide polymorphisms (SNPs). The logistic regression model was utilized to estimate associations of T2DM-related SNPs and wGRS with lung cancer risk. Sensitivity analyses were also performed to assess the robustness of the observed associations. Results We found no evidence for a causal relationship between T2DM and lung cancer risk (odds ratio, OR = 0.96, 95% confidence interval: 0.91–1.01, p = 0.96), and the association did not vary among populations of different age, sex, smoking status, and histological type. Sensitivity analyses (e.g., MR-Egger test) suggest that pleiotropic effects did not bias the result. Conclusion In this MR study with a large number of lung cancer cases, we found no evidence to support the causal role of T2DM in lung cancer risk. Further large-scale prospective studies are warranted to replicate our findings.